Respostas

2014-06-11T15:38:57-03:00
Aplica-se fator comum em evidencia e temos:
x.(2x + 6) = 0 
Assim:   x=0   ou 2x+6=0  
                            2x= -6 
                             x= -3 
2 4 2
2014-06-11T15:42:02-03:00
2x² + 6x=0               0nde     a =2     b=6     c=0

Δ=b²-4.a.c
Δ=6²-4.2.0
Δ=36-0
Δ=36  ⇒ raiz de 36 é 6



x'=-6 + 6    0
    ¨¨¨¨¨¨¨¨ =¨¨¨¨¨= 0
      2.2       4


x"=-6-6     -12 
     ¨¨¨¨¨¨¨= ¨¨¨¨¨¨ =  3
       2.2      4                                         S;(0, 3)

Bons estudos!



1 4 1